2019
DOI: 10.1039/c9ra04662c
|View full text |Cite
|
Sign up to set email alerts
|

Study on microwave assisted extraction of chrysophanol and its intervention in biofilm formation of Streptococcus suis

Abstract: A microwave assisted extraction technology was used to extract chrysophanol from rhubarb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Figure 7(a) showed that SP significantly inhibited the biofilm formation of S. suis ( p < 0.05) at the concentrations of 1/2, 1/4 and 1/8 MIC, confirming that sub-inhibitory concentrations of SP effectively interfered with the biofilm formation of S. suis . Furthermore, SP displayed more efficient inhibitory effect on biofilm formation than rutin and chrysophanol (Bai et al , 2019; Liu et al , 2018). Therefore, SP might be used to treat the diseases spread through S. suis biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7(a) showed that SP significantly inhibited the biofilm formation of S. suis ( p < 0.05) at the concentrations of 1/2, 1/4 and 1/8 MIC, confirming that sub-inhibitory concentrations of SP effectively interfered with the biofilm formation of S. suis . Furthermore, SP displayed more efficient inhibitory effect on biofilm formation than rutin and chrysophanol (Bai et al , 2019; Liu et al , 2018). Therefore, SP might be used to treat the diseases spread through S. suis biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Another phenolic compound found within Rheum palmatum that also demonstrates antibiofilm activity is chrysophanol ( 11 ). 67 This study reports inhibition of biofilm formation (around 60%) in Staphylococcus suis at concentrations as low as 0.112 μg mL −1 . SEM results demonstrated a single molecule state of the bacteria cells with a lack of interconnection to create a biofilm, however, the exact mechanism of antibiofilm action needs to be further explored.…”
Section: Plant-derived Natural Products With Antimicrobial Activitymentioning
confidence: 84%
“…It is noteworthy that drug residues in pig and human, multiple resistance, allergy, and gastrointestinal bleeding and other problems would arise after long-term application of common antibiotics [ 22 ]. Therefore, the development and utilization of natural products with antibacterial and antibiofilm properties is particularly urgent [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%